Comprehensive thermal performance analysis and optimization study on U-type deep borehole ground source heat pump systems based on a new analytical model. (1st July 2023) - Shen, Junhao; Zhou, Chaohui; Luo, Yongqiang; Tian, Zhiyong; Zhang, Shicong; Fan, Jianhua; Ling, Zhang
Abstract: U-type deep borehole heat exchangers (UDBHEs) can provide low-carbon heating for buildings utilizing medium-deep geothermal energy. This study presents a new analytical model based on the Segmented Finite Line Source (SFLS) method to investigate the heat transfer process of a UDBHE. The developed model is verified by comparing with experimental results. Subsequently, the soil and fluid temperature are analyzed, and the influences of design and operation parameters on UDBHE performance are investigated. The results indicate that the heat extraction capacity increases as the higher thermal conductivity of backfill material, pipe diameter and flow rate. We identify a linear correlation between the horizontal or vertical borehole length and the heat extraction rate. In addition, an integrated model for the optimization study on the U-type deep borehole ground source heat pump (UDBGSHP) system is presented, which comprehensively considers the dynamic heating loads of the buildings and the dynamic heat transfer process in the UDBHEs. With the control method, the electricity consumption of the heat pump decreases from 5110 kWh to 4812 kWh within a 72-h operation. This work can offer guidance for the design and optimization of UDBGSHP systems. Highlights: An analytical heat transfer model for U-type deep borehole is established. The soil and fluid temperature field of U-type deep borehole is analyzed. Influences of design and operation parameters on the system performance. U-type deep borehole ground source heat pump system is optimized.